Remuneración docente en el cantón La Maná - Pilamunga Masapanta, Blanca Yolanda (2017)
In recent years there have been substantial changes in education where it can be stated that in Ecuador the salaries are given according to the category that the Ministry of Education raises. Where after extensive preparation of teachers are able to serve society, the same that would lead to a better wage income. The salary of a teacher depends on several factors such as: academic qualification, professional development, length of service and finally the results obtained in the evaluation processes, in the same way the teacher has been part of a ladder, which guarantees a fair and dignified remuneration within the new legal educational framework. Professional performance has a great influence on the benefit to society, so the remunerations should also be of a high degree of satisfaction for teachers, who are exposed to not being paid correctly....